A Monetary and Political History of the Phoenician City of Byblos in the Fifth and Fourth Centuries B.C.E. - Elayi, Josette 1943-; Elayi, Alain G. 1943- (Book collections on Project MUSE., 2014)
"In A Monetary and Political History of the Phoenician City of Byblos, the Elayis' tour de force is the coin catalog, which introduces 1,662 silver Byblian coins, also displayed in 25 pp. of photos. Besides the usual numismatic analysis (monetary production, number of issues, manufacturing techniques, and processes), this impressive volume provides information on monetary inscriptions and iconography and on the history of Byblos. Significantly, it reveals new information on the Persians' western policy and the history of the other Phoenician cities as well as on craftsmen in the Levant, and thus the book is an indispensable reference for understanding coin circulation, trading exchanges, and even the wars that occurred with the Greeks, Cypriots, and Egyptians in the Phoenician eastern Mediterranean"--Provided by publisher